Customer Journey and Experience in Railways Public Transport: A Systematic Literature Review and Subsequent Research Agenda - Ratnasari, Nissa Ghulma (Yayasan Riset dan Pengembangan Intelektual, 2024)
Customer journey has become an increasingly important concept for understanding complex customer behaviour and gaining insights into their experiences. While this term has been used in various disciplines since the 1990s and has evolved. This paper adopts a stream-based systematic review approach to identify the underlying themes of the customer journey presented in the business literature through 2024. Initial set of search keywords are “customer journey” or “consumer journey”. And then “railways” or “rails”, as additional search string. 82 relevant papers were taken from Scopus for analysis. Linking the user customer journey in public transportation is crucial today. This study aims are (1) mapping existing studies on customer journey analysis in the railway industry, including reference journal sources, study context, country of origin and year of publication of bibliographic journals (previous research), (2) compiling definition terminology regarding customer journey stated by previous researchers' thoughts, (3) identifying important variables that influence customer experience throughout their journey on the train, (4) mapping existing studies on customer journey analysis in the railway industry, based on the approaches that have been developed in, (5) classifying studies related to customer journey in railways, related to research methods that have been used in previous research, (6) provide topics and previous research results that can be used as a framework by researchers and practitioners as a reference in developing service improvement strategies in the railway industry (7) identify research gaps that can be the basis for further research related to customer journey analysis in this sector. For methodology, methodological diversity in research that includes exploration, description, experimentation, and causal analysis. The positivist paradigm dominates, but there is a balance with the interpretivist paradigm in more exploratory studies. The inductive approach is often used for exploratory studies, while deduction is more suitable for testing existing theories. So now, the relevance of the importance of the presence of public transportation is increasing day by day in the activities of modern society. The development of public transportation in developing countries is getting higher, in line with population growth through urbanization.